Generation of nonclassical optomagnonic states under the influences of Stokes scattering process and thermal noise - E. Ghasemian; M. K. Tavassoly (Scientific Reports)
Abstract We present a theoretical model for a hybrid optomagnonic system, i.e., a ferromagnetic YIG sphere that supports two optical modes and a magnon mode. The system is considered under the influences of dissipation process, thermal noise, and the Stokes scattering process. In particular, the quantum statistics of particles is evaluated via the dynamical evolution of their respective second-order correlation functions. Generally, the system can provide strong nonclassical features such that both strong antibunching and blockade effects can be realized in the patterns of the photon and magnon quantum statistics. Since the particles lose their nonclassical features in the presence of environmental effects, therefore a quantum-classical crossover takes place, i.e., the antibunched photons are transformed into the bunched particles. Such a crossover may be expected in the patterns of magnon statistics, too. Applying a weak driving field accompanied with a small value of the reorganization parameter facilitates the magnon blockade effect and strong magnon antibunching. Our analyses show that thermal noise degrades the nonclassical features stemming from the individual system components (auto-correlation). In contrast, thermal noise may provide a larger window for realizing the nonclassical properties originated from the joint system components (cross-correlation). Interestingly, when the system includes a small number of particles both correlation and anti-correlation features may be enhanced even in the presence of thermal noise. The nonclassical optomagnonic states can be utilized in various applications, including quantum information processing, sensing, and the study of fundamental quantum mechanics.